Metode Ulama’ Mutaqaddimīn dan Muta'akhirīn dalam Ta'līl Ḥadīṡ: Studi Komparatif Pemikiran al-Dāruquṭnī dan al-Albānī - Iqbal Nursyahbani; Fahmi Husen; Muhammad Alamudin; Ahmad Nurhamdani; Ahmad ‘Ubaydi Hasbillah (Jurnal Dirosah Islamiyah, 2024)
This study aims to compare the ta'lil (causality) method used by two great scholars in the field of hadith, namely al-Daruqutni and al-Albani. The ta'lil method is an approach used to classify hadiths based on their strength or weakness. They both represent two different periods in the history of hadith, namely the ulama' mutaqaddimīn (early period) and the ulama' muta'akhirīn (modern period). This study uses a comparative approach by analyzing the written works of the two scholars. The results of the study show that these two 'ulama', despite coming from different eras, both have a deep concern for hadith. They also have their own methods in knowing the 'illat (defects) that exist in the hadith. Imam al-Dāruquṭnī's method in researching 'illat in a hadith is focused on research in the sanad or the narrators of the hadith. He also considers that the study of al-jarḥ wa al-ta'dīl (criticism and authentication of narrators) is also included in the study of the 'illat of hadith, so al-Dāruquṭnī often examines the hadith narrators from that perspective. Meanwhile, Shaykh al-Albānī has a more in-depth research method on the 'illat in the hadith. He is not only focused on the study of the 'illat of hadith in terms of the sanad and narrators, but his study also touches on the research of the matn (text) of the hadith. Therefore, it becomes reasonable that al-Dāruquṭnī is more lenient in determining the validity of a hadith, and al-Albānī is more strict in determining the validity of a hadith. Keywords: Ta’līl; Hadith; al-Dāruquṭnī; al-Albānī